2019
DOI: 10.5694/mja2.50129
|View full text |Cite
|
Sign up to set email alerts
|

Biology and therapy of multiple myeloma

Abstract: Summary Genetic sequencing of the myeloma genome has not revealed a specific disease‐determining genetic alteration. Multiple disease subclones exist at diagnosis and vary in clinical importance with time and drug sensitivity. New diagnostic criteria have identified indications for early introduction of therapy. Autologous stem cell transplantation remains an essential component of therapy in young and fit patients. The use of continual suppressive (maintenance) therapy has been established as an important c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
75
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(75 citation statements)
references
References 66 publications
0
75
0
Order By: Relevance
“…Surprisingly, the expression of fully functional proteins typical of the HPT axis and in particular of the TSH and TRH receptors has been found in human skin and in HFs [ 27 ]. Receptors for TSH and TRH in the skin induce the expression of skin-specific genes [ 28 ] and thus regulate epidermal physiology, adding a mechanistic explanation of the correlation between the altered TH status and the most common dermatology diseases [ 29 ].…”
Section: Thyroid Hormone Action and Metabolismmentioning
confidence: 99%
“…Surprisingly, the expression of fully functional proteins typical of the HPT axis and in particular of the TSH and TRH receptors has been found in human skin and in HFs [ 27 ]. Receptors for TSH and TRH in the skin induce the expression of skin-specific genes [ 28 ] and thus regulate epidermal physiology, adding a mechanistic explanation of the correlation between the altered TH status and the most common dermatology diseases [ 29 ].…”
Section: Thyroid Hormone Action and Metabolismmentioning
confidence: 99%
“…Therefore, early diagnosis of MM is of great significance to improve the prognosis. Due to the different experience of different doctors, the master scale of diagnostic criteria and diagnosis and treatment level are not the same and the clinical misdiagnosis rate is high [6]. In our study, the results showed that 81.9% MM patients had more than 10% of plasma cells, while only 64.5% than that detected by flow cytometry.…”
Section: Discussionmentioning
confidence: 60%
“…Pericardial effusion is a rare manifestation of metastatic extramedullary multiple myeloma . Less than 1% of all multiple myeloma cases present with cardiac involvement, and presentation of cardiac tamponade is even rarer .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple myeloma is a malignancy of plasma cells originating from the bone marrow, which constitutes 10% of all haematological cancers . Extramedullary disease in multiple myeloma occurs 6–20% of the time.…”
Section: Introductionmentioning
confidence: 99%